'Counselling is not just providing information': perceptions of caregivers and stakeholders on the design of nutrition and health counselling interventions for families with young children in rural Kenya - Kihagi, Grace Wothaya; Hansen, Lea-Sophie; Agure, Erick; Muok, Erick M. O.; Mank, Isabel; Danquah, Ina; Sorgho, Raissa (BMC health services research, 2024)
BACKGROUND: Globally, a fifth of the children continue to face chronic undernutrition with a majority of them situated in the Low- and Middle-Income Countries (LMIC). The rising numbers are attributed to aggravating factors like limited nutrition knowledge, poor feeding practices, seasonal food insecurity, and diseases. Interventions targeting behaviour change may reduce the devastating nutrition situation of children in the LMICs. - OBJECTIVE: For the co-design of a Behaviour Change Communication (BCC) intervention for young children in rural Kenya, we aimed to identify the experiences, barriers, facilitators, and preferences of caregivers and stakeholders regarding nutrition and health counselling. - DESIGN: We employed a qualitative study design and used a semi-structured interview guide. The in-depth interviews were recorded, transcribed, and analysed using content analysis, facilitated by the software NVivo. - SETTING: Health and Demographic Surveillance System (HDSS) area in Siaya County, rural Kenya. - PARTICIPANTS: We interviewed 30 caregivers of children between 6 and 23 months of age and 29 local stakeholders with experience in implementing nutrition projects in Kenya. - RESULTS: Nutrition and health counselling (NHC) was usually conducted in hospital settings with groups of mothers. Barriers to counselling were long queues and delays, long distances and high travel costs, the inapplicability of the counselling content, lack of spousal support, and a high domestic workload. Facilitators included the trust of caregivers in Community Health Volunteers (CHVs) and counselling services offered free of charge. Preferences comprised (1) delivering of counselling by CHVs, (2) offering individual and group counselling, (3) targeting male and female caregivers. - CONCLUSION: There is a disconnect between the caregivers' preferences and the services currently offered. Among these families, a successful BCC strategy that employs nutrition and health counselling should apply a community-based communication channel through trusted CHVs, addressing male and female caregivers, and comprising group and individual sessions.